2004
DOI: 10.1504/ijmc.2004.005856
|View full text |Cite
|
Sign up to set email alerts
|

Wireless in the enterprise: requirements, solutions and research directions

Abstract: In the last few years, wireless networking has seen considerable interest among service providers, users, vendors and content developers. Significant advances have been made in devices, applications, middleware and networking infrastructure. With wireless becoming such a mainstream technology, there is a growing interest in increasing its usage in the enterprise environment. Before wireless solutions can be deployed widely, the requirements of the enterprise environment and capabilities and limitations of wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…Scholars have provided conceptual overviews of the industry value chain (Barnes 2002), identified development and research issues (Tarasewich, Nickerson and Warkentin 2002, Varshney, Malloy, Jain and Ahluwalia. 2002, Varshney and Vetter 2001, conceptualized business models for telecommunication services providers, devices and applications (Haaker et al 2004, Varshney andVetter 2001), identified strategies for system development (Kemper andWolf 2003, Krogstie et al 2004), and detailed development cost and infrastructure standards (Balasubramaniam et al 2001).…”
Section: Mobile Ismentioning
confidence: 99%
See 4 more Smart Citations
“…Scholars have provided conceptual overviews of the industry value chain (Barnes 2002), identified development and research issues (Tarasewich, Nickerson and Warkentin 2002, Varshney, Malloy, Jain and Ahluwalia. 2002, Varshney and Vetter 2001, conceptualized business models for telecommunication services providers, devices and applications (Haaker et al 2004, Varshney andVetter 2001), identified strategies for system development (Kemper andWolf 2003, Krogstie et al 2004), and detailed development cost and infrastructure standards (Balasubramaniam et al 2001).…”
Section: Mobile Ismentioning
confidence: 99%
“…Based on the notion that mobile IS combine traditional computing functionality with interpersonal communication functionality (Balasubramaniam et al 2001, Krogstie et al 2004, Sarker and Wells 2003, Varshney et al 2002, we categorize mobile IS functionality according to two dimensions, namely (1) whether the main focus is on interpersonal interaction or on computing, and (2) whether the direction of the interaction between the user and the system is one-way or two-way interactive (reciprocal) (Balasubramaniam et al 2001). The resulting classification scheme includes four functionalities (Gebauer andShaw 2004, similar: Yuan and, as described and exemplified in Table 1.…”
Section: Functionalitymentioning
confidence: 99%
See 3 more Smart Citations